Financing Post-Disaster Recovery and Reconstruction Operations : Developing an Institutional Mechanism to Ensure the Effective Use of Financial Resources - World Bank (Washington, DC, 2015)
This guidance note provides policy makers with an operational framework to establish an institutional mechanism for financing post-disaster recovery and reconstruction operations. It is based on international experience, in particular that of Mexico due to its pioneering initiatives to develop comprehensive disaster risk management programs, including the fiscal management of disaster risks. The guidance note consists of six key steps to ensure effective procedures for resource mobilization, allocation, and execution. It serves as an outline for a series of six short notes, provided separately, which offer further detail on each of the six key steps. The six accompanying short notes provide guidance to: (i) quantify (implicit and explicit) contingent liabilities associated with natural disasters; (ii) formalize the process for declaration of disasters and financing contingent liabilities; (iii) clarify post-disaster financial responsibilities of the central and local governments; (iv) mobilize resources ex-ante through a DRM fund and financial protection strategy; (v) allocate resources based on damage and loss assessment methodology; and (vi) execute resources and coordinate efforts across the post-disaster recovery and reconstruction process.